Cause-and-effect analysis dalam pembuatan website integrasi untuk mengatasi tantangan promosi Desa Banyuwangi - Pertiwi, Fungky Dyan; Badiuzzaman, Harith; Rasyid, Al Mushhaf Fahlul; Luhur, Abyan Estu; Azzidani, Muhammad Aziz; Zavitra, Al Aufairuzsyah Aswyn (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
The rapid advancement of technology has enabled the presentation of information practically and systematically that can be accessed by diverse groups of people. One of the essential types of information needed by the public is related to areas they intend to visit without having to be physically present beforehand. In response to these technological developments, an integrated website serves as an effective medium to provide the required information while simultaneously functioning as a platform for regional promotion. Beyond village promotion, the integrated website also benefits local business actors by enabling them to create business profiles. The cause-and-effect method using a fishbone diagram was applied as a systematic approach to address the promotional challenges faced by Banyuwangi Village and to provide solutions through the development of the integrated website. This method illustrates each underlying condition contributing to the problem, allowing appropriate countermeasures to be identified. The project resulted in the integrated website www.desabanyuwangi.com, which serves as a platform to showcase the village’s tourism, natural resources, and local businesses. In addition, training on Google Business was provided to local MSMEs to improve their digital literacy and expand their market reach. Overall, the program not only produced a tangible technological output but also fostered community empowerment through digital capacity building.